2016
DOI: 10.1111/jomf.12284
|View full text |Cite
|
Sign up to set email alerts
|

Couple Resilience to Economic Pressure Over Time and Across Generations

Abstract: Research suggests that economic stress disrupts perceived romantic relationship quality; yet less is known regarding the direct influence of economic stress on negative behavioral exchanges between partners over time. Another intriguing question concerns the degree to which effective problem-solving might protect against this hypothesized association. To address these issues, the authors studied two generations of couples who were assessed approximately 13 years apart (Generation 1: N = 367, Generation 2: N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 54 publications
5
77
0
4
Order By: Relevance
“…These findings underscore the buffering effect of intimate relationships for those with chronic illnesses and highlights how intimate unions may serve as a protective factor for diabetic individuals (Berg & Upchurch, ; Johnson et al, ). Our study also extends research on the dyadic experience of couples facing economic pressure (Conger et al, ; Masarik et al, ) by identifying a growing subpopulation of couples who may experience high levels of economic pressure due to the direct and indirect costs accrued from living with type 2 diabetes. Yet this study shows that problem‐solving communication, particularly by the nondiabetic spouse, helps increase the confidence both partners have about successfully managing the illness by decreasing the emotional distress associated with economic pressure.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…These findings underscore the buffering effect of intimate relationships for those with chronic illnesses and highlights how intimate unions may serve as a protective factor for diabetic individuals (Berg & Upchurch, ; Johnson et al, ). Our study also extends research on the dyadic experience of couples facing economic pressure (Conger et al, ; Masarik et al, ) by identifying a growing subpopulation of couples who may experience high levels of economic pressure due to the direct and indirect costs accrued from living with type 2 diabetes. Yet this study shows that problem‐solving communication, particularly by the nondiabetic spouse, helps increase the confidence both partners have about successfully managing the illness by decreasing the emotional distress associated with economic pressure.…”
Section: Discussionsupporting
confidence: 64%
“…These findings underscore the buffering effect of intimate relationships for those with chronic illnesses and highlights how intimate unions may serve as a protective factor for diabetic individuals (Berg & Upchurch, 2007;Johnson et al, 2013). Our study also extends research on the dyadic experience of couples facing economic pressure (Conger et al, 1999;Masarik et al, 2016) by identifying a growing subpopulation of couples who may experience high levels of economic pressure due to the direct and indirect costs accrued from living with type 2 diabetes.…”
Section: Discussionsupporting
confidence: 62%
“…In other words, to the extent that couples residing in stressful contexts are able to communicate effectively and successfully manage their problems together, they should be less likely to exhibit declines in their marital quality over time [23]. Yet, growing research indicates that the experience of stress may render spouses ill-equipped to face an increase in relational challenges.…”
Section: Route 2: Stressful Contexts Hinder Constructive Responses Tomentioning
confidence: 99%
“…For example, stress seems to impede effective problem-solving, as couples experiencing greater financial strain are less constructive when discussing their marital problems than are couples who are more financially secure [27]. Specifically, studies of observed marital interactions have linked economic hardship to increases in couples’ hostile and contemptuous behaviors [23], decreases in marital warmth [28], and the more frequent use of demand/withdraw communication patterns, a maladaptive pattern in which one spouse denigrates or makes demands of the partner, while the partner responds by refusing to discuss the issue or becoming defensive [29]. Additional studies suggest that stress also may impair effective support provision within the marriage.…”
Section: Route 2: Stressful Contexts Hinder Constructive Responses Tomentioning
confidence: 99%
“…In the economic context of the family, theories from economics and sociology suggest that changes to economic circumstances affect parents and children through the following two primary pathways: (a) changes in consumption and the related investments a family can make to support children's development (Bradley & Corwyn, 2002;Mayer, 1997) and (b) stress and its effects on family conflict and parenting (Conger et al, 2010;Masarik et al, 2016;McLoyd, Jayaratne, Cebaloo, & Borquez, 1994;Mistry et al, 2002).…”
Section: Income Volatility As a Distinct Form Of Economic Disadvantagementioning
confidence: 99%